SIMPLE CANVA DESIGN TRAINING FOR SCHOOL DEVELOPMENT AT RESTU IBU ISLAMIC KINDERGARTEN AND ELEMENTARY SCHOOL - Purwitasari, Fadilla; Ariska, Ricky Angga; Yuliarini, Sarah (Journal of Social Comunity Services, 2024)
Objective: This study aims to address the challenges faced by schools with limited budgets in providing attractive, two-dimensional learning media by offering training in Canva as a cost-effective design solution. Methods: Community service activities were conducted, including structured workshops that trained teachers from Restu Ibu Islamic Kindergarten and Elementary School, Malang City, in utilizing the Canva platform to create visually engaging and budget-friendly learning media. Results: The training received a positive response, and teachers continued applying their skills up to a year later, effectively integrating Canva-based designs into their instructional materials. Novelty: This approach highlights the use of accessible digital tools like Canva to empower educators in financially constrained environments, promoting sustainable use of digital design skills for enhancing educational quality. The study demonstrates that practical design training can serve as a viable, long-term solution for schools in need of affordable yet visually engaging learning media.